2012
DOI: 10.1007/s11064-011-0700-2
|View full text |Cite
|
Sign up to set email alerts
|

Classic 18.5- and 21.5-kDa Myelin Basic Protein Isoforms Associate with Cytoskeletal and SH3-Domain Proteins in the Immortalized N19-Oligodendroglial Cell Line Stimulated by Phorbol Ester and IGF-1

Abstract: The 18.5-kDa classic myelin basic protein (MBP) is an intrinsically disordered protein arising from the Golli (Genes of Oligodendrocyte Lineage) gene complex and is responsible for compaction of the myelin sheath in the central nervous system. This MBP splice isoform also has a plethora of post-translational modifications including phosphorylation, deimination, methylation, and deamidation, that reduce its overall net charge and alter its protein and lipid associations within oligodendrocytes (OLGs). It was or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 34 publications
(62 citation statements)
references
References 95 publications
(152 reference statements)
3
58
0
Order By: Relevance
“…These minor MBP isoforms have been observed in the nucleus of primary OLG cultures and OLGs in the mouse brain [25][26][27] and are also enriched in the radial component of compact myelin [28,29]. We have found that full-length 21.5-kDa MBP was still localized primarily to the nucleus despite the presence of the 3′UTR [20][21][22]. The minor isoforms have been speculated to play key developmental roles that may regulate myelinogenesis [25,27,[30][31][32].…”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…These minor MBP isoforms have been observed in the nucleus of primary OLG cultures and OLGs in the mouse brain [25][26][27] and are also enriched in the radial component of compact myelin [28,29]. We have found that full-length 21.5-kDa MBP was still localized primarily to the nucleus despite the presence of the 3′UTR [20][21][22]. The minor isoforms have been speculated to play key developmental roles that may regulate myelinogenesis [25,27,[30][31][32].…”
Section: Introductionmentioning
confidence: 78%
“…This cell line stains positive for both the NG2 and A2B5 antigens, which are markers for oligodendroglial progenitor cells (OPCs), and lacks expression of classic MBP and proteolipid protein mRNAs [35]. The N19-OLG line has been successfully employed in other studies, including specifically examining the effect of Golli and classic 18.5-kDa MBP over-expression on calcium homeostasis [13,20,40,41], and on the co-localization of 18.5-kDa MBP with cytoskeletal proteins and SH3-domain-containing proteins [21,22].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations